Multi and transculturality between Jesuits and native peoples during the Argentine colonial era - Güemes, Luciana Acosta; Calzetta, María Inés; Milán, Carolina Giménez (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
The development of this work aims to identify the type of cultural relationship between Jesuits and native settlers during the colonial era in the Argentine national territory, the latter defined by the period in which there was socioeconomic and political control by the Spanish crown; until national independence in 1816. To do this, we will begin by contextualizing the definitions of culture, interculturality, multiculturalism and transculturality, to identify what type of cultural relationships took place between the actors in said historical context. Starting from the basic assumption that there was no true intercultural transfer given the subordination of the native peoples, the existence of processes of multiculturalism and interculturality will nevertheless be postulated. Next, the origin and development of Jesuit action within the Argentine national territory during the colonial era will be addressed, with special emphasis on its educational characteristics as an argument for the existence of multiculturalism. Finally, an example of interculturality represented by the knowledge of the native peoples will be developed regarding the use of healing plants in the Jesuit pharmacopoeia, once used by these peoples.